Isomerization of Glucose into Fructose and Mannose in Presence of Anion-Exchanged Resins - Lv, Lingjuan; Guo, Xianghai; Bai, Peng; Zhao, Shuo (Asian Journal of Chemistry, 2015)
Much attention has been paid to the conversion of bio-regenerable glucose into valuable chemicals and liquid fuels, like fructose, 5-hydroxymethyl furfural (5-HMF), mannose and levulinic acid. The isomerization of glucose into fructose and mannose simultaneously was studied in the presence of commercial anion-exchanged resins. An OA16 (45) orthogonal experiment was designed investigating the following four variables i.e., resin types (factor A), reaction temperature (factor B), pH value (factor C) and D-glucose to resin ratio (factor D). Reaction temperature was identified as a prominent factor of this transformation. Ideal conversions and selectivities were obtained even in the case of high glucose concentration. In contrast to other catalysts reported like Tin-beta, anion-exchanged resins highlight by reasonable catalytic activity and selectivity under mild conditions, easy regeneration and separation and low cost. Further efforts were worthwhile in this area.